2016
DOI: 10.1016/j.rpor.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

A novel dynamic field-matching technique for treatment of patients with para-aortic node-positive cervical cancer: Clinical experience

Abstract: IMRTTreatment planning a b s t r a c t Aim: To report outcomes for patients with para-aortic lymph node positive cervical cancer treated with a dynamic field-matching technique.Background: PET staging of cervical cancer has increased identification of patients with para-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…Regardless, toxicity is also a concern and have been previously reported [19] in smaller retrospective studies. The impact of intensity modulated radiotherapy (IMRT) or arc therapy in lowering the toxicity rates has been demonstrated in some small studies as well [12][13][14][15][20][21][22]. In the United States, Osborn et al (2018) [23], in a study with 103 patients, showed how technology may impact survival on positive PAN cervical cancer patients, particularly the use of 18 FDG-PET scans for diagnosis and staging and IMRT technique for treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Regardless, toxicity is also a concern and have been previously reported [19] in smaller retrospective studies. The impact of intensity modulated radiotherapy (IMRT) or arc therapy in lowering the toxicity rates has been demonstrated in some small studies as well [12][13][14][15][20][21][22]. In the United States, Osborn et al (2018) [23], in a study with 103 patients, showed how technology may impact survival on positive PAN cervical cancer patients, particularly the use of 18 FDG-PET scans for diagnosis and staging and IMRT technique for treatment.…”
Section: Resultsmentioning
confidence: 99%